2021
DOI: 10.1002/ente.202100085
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Scalable Synthesis of LiNi0.5Mn1.5O4 Cathode by Sol–Gel‐Assisted Microwave Sintering

Abstract: High‐voltage spinel LiNi0.5Mn1.5O4 (LNMO) is a promising cathode material for high‐energy‐density and high‐power‐density lithium‐ion batteries (LIBs). The high cost of the currently available LIBs needs to be addressed urgently for wide application in the transport sector (electric vehicles, buses) and large‐scale energy storage systems (ESS). Of significance, herein, novel fast and scalable microwave‐assisted synthesis of LNMO is reported, which leads to a production cost cut. X‐ray diffraction (XRD) analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The XRD patterns revealed distinct well-matched peaks of the cubic spinel LiNi 0.5 Mn 1.5 O 4 phase (LNMO, ICDD/PDF4#01-080-2984) with the Fd-3m space group in addition to a trace amount of an impurity of the rock-salt Li 0.5 Ni 0.5 O phase (LNO, ICDD/PDF4#04-007-6739), which is typically present in LNMO [27]. The spinel and rock salt phases, which are commonly denoted as AB 2 O 4 and AB 2 O 3 , can be reversibly transformed by the following equations regarding the oxygen loss during synthesis [31]. Furthermore, studies have also demonstrated that the existence of this phase was due to the reduction in a part of the Mn in the LNMO from Mn 4+ to Mn 3+ during high-temperature calcination to maintain the charge balance, while the disordered phase is formed due to the loss of Li [32].…”
Section: Resultsmentioning
confidence: 99%
“…The XRD patterns revealed distinct well-matched peaks of the cubic spinel LiNi 0.5 Mn 1.5 O 4 phase (LNMO, ICDD/PDF4#01-080-2984) with the Fd-3m space group in addition to a trace amount of an impurity of the rock-salt Li 0.5 Ni 0.5 O phase (LNO, ICDD/PDF4#04-007-6739), which is typically present in LNMO [27]. The spinel and rock salt phases, which are commonly denoted as AB 2 O 4 and AB 2 O 3 , can be reversibly transformed by the following equations regarding the oxygen loss during synthesis [31]. Furthermore, studies have also demonstrated that the existence of this phase was due to the reduction in a part of the Mn in the LNMO from Mn 4+ to Mn 3+ during high-temperature calcination to maintain the charge balance, while the disordered phase is formed due to the loss of Li [32].…”
Section: Resultsmentioning
confidence: 99%
“…Instead of conventional calcination, microwave-based quick calcination was adapted for a fast and scalable synthesis approach. 123 Due to rapid calcination, the material is free from bulk agglomeration, with particle size distribution ranging from 50 to 150 nm. The D-700 material, as shown in Fig.…”
Section: Transition Metal Oxide Nanomaterialsmentioning
confidence: 99%
“…To improve the performance of LNMO, synthesis methods such as solid phase, sol-gel, molten salt, co-precipitation, and microwave synthesis have been developed. [10][11][12][13][14] Among these synthesis methods, co-precipitation is effective in preparing pure LNMO with high electrochemical performance because it allows the mixing of Ni and Mn sources at the atomic level. 15 Additionally, the spherical hierarchical particle morphology of LNMO provides an isotropic diffusion path between the particle bulk and the surface, which can reduce resistance.…”
mentioning
confidence: 99%